Zastosowanie podejścia procesowego w urzędach administracji samorządowej - Szumowski, Witold (The Application of a Process Approach in Self-Government Offices, 2009)
The application of modern management instruments is not limited only to business sector. Poland's joining the European Union in 2004, which brings along bigger opportunities to absorb the EU funds as well as raising both office clerks and customers' awareness, causes public administration's bigger and bigger interest in the application of modern management methods and concepts. The same holds true for the process approach. The evaluation of the interest in this concept as well as the scope of organizational changes in public administration offices seem to be quite an interesting question. The author of the paper undertook such research and its subject was the application of the process approach in local administration offices. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 106-118